Islamic Education Model-Based Quality Assurance: A Case Study in Sekolah Mutiara Bali - Yasin, Muhamad; Himam, M. Muafi (Didaktika Religia, 2019)
This study seeks to describe Islamic education learning strategies that are modern and based output. By carrying the principle out of the box, the Islamic schools Sekolah Mutiara in Bali can lift Islamic education as a role model in other schools, especially in combining general studies with religion. The significance of this study lies in the base of the quality of education (quality assurance) which drafted carefully, where the quality of the primary standard used to print generation (students). With the model of qualitative approach was descriptive documentation, then the data is taken based on observation and documentation, then after analysis of data obtained through triangulation technique several important findings. 1) Implementation of quality assurance in Islamic schools â€œMutiaraâ€ School can be seen in three aspects. First, learning model. The model is applied to the school is the social internalization of Islam, where all of the subject matter infiltrated by Islamic values. Second, habituation, ie habituation speaking, how to behave and interact with others coupled with morals and character. Third, skill training, where learners are given targets following the needs of the times like making machines, robot or any other technological tool. 2) the integrated curriculum. The curriculum used is the 2013 curriculum combined with the Islamic curriculum (JSIT Indonesia). By combining both this curriculum, then the resulting output can be the generation that controls the common knowledge in all its aspects. 3) The competence of educators. By looking at the methods and curriculum that are taken, then educators must be qualified to master and understand all the sciences.